2022
DOI: 10.1016/j.crphys.2022.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic patterns associated with activation of bradykinin-sensitive pericardial afferents

Abstract: The heart is endowed with reflexogenic areas capable of powerful blood pressure responses. Relatively little work has studied the hemodynamic mechanisms underlying these responses and whether these are sexually dimorphic. We hypothesized that activation of bradykinin-sensitive pericardial afferents would produce a sexually dimorphic cardiac output response. Male and female Sprague Dawley rats were anesthetized and instrumented with catheters for recording arterial pressure, with an aortic arch flow probe to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Nevertheless, it seems logical that a CSAR‐driven increase in MCFP will lead to an increase in cardiac output. Indeed, CSAR stimulation was reported to increase cardiac output by approximately 14% in the rat (Wang et al, 2017) and we reported that pericardial BK injection increased cardiac output by 12%–20% in male and female rats, respectively (Martin et al, 2022). Thus, activation of bradykinin‐sensitive afferents in the pericardial space induces a venoconstrictor response of sufficient magnitude to influence systemic hemodynamics.…”
Section: Discussionmentioning
confidence: 86%
“…Nevertheless, it seems logical that a CSAR‐driven increase in MCFP will lead to an increase in cardiac output. Indeed, CSAR stimulation was reported to increase cardiac output by approximately 14% in the rat (Wang et al, 2017) and we reported that pericardial BK injection increased cardiac output by 12%–20% in male and female rats, respectively (Martin et al, 2022). Thus, activation of bradykinin‐sensitive afferents in the pericardial space induces a venoconstrictor response of sufficient magnitude to influence systemic hemodynamics.…”
Section: Discussionmentioning
confidence: 86%